Exploring the Role of MAPK3 in Major Depressive Disorder: Molecular Docking, Dynamics, and Binding Free Energy Analysis of Natural Compounds as Alternatives to Conventional Drugs - Abhimanyu Chauhan; Chakresh Kumar Jain (International Journal of Bioinformatics and Computational Biology, 2025)
Major Depressive Disorder (MDD) is a prevalent neuropsychiatric disorder with limited treatment efficacy and significant side effects associated with conventional antidepressants. Recent studies have highlighted the role of mitogen-activated protein kinase 3 (MAPK3) in the mechanisms underlying MDD, positioning it as a potential target for the development of novel therapeutic drugs. In this study, we employed various computational approaches to explore natural compounds as viable alternatives to synthetic antidepressants. Researchers used several advanced methods—like molecular docking, ADMET analysis, molecular dynamics simulations, and binding energy calculations (MM-GBSA)—to study how these natural compounds interact with the MAPK3 protein. Out of all the compounds tested, Cannflavin A showed the strongest ability to bind with the target protein and had favorable pharmacokinetic properties, which is why it was chosen for more detailed study. To gain deeper insight into its function, researchers conducted Gene Ontology (GO) enrichment and Protein-Protein Interaction (PPI) network analyses for MAPK3. The GO analysis revealed significant enrichment in biological processes such as the ERK1 and ERK2 cascade, thyroid gland development, lung morphogenesis, and positive regulation of miRNA maturation, reinforcing its involvement in cellular signaling and neurobiological pathways. The PPI analysis identified key interactions between MAPK3 and regulatory proteins such as MAP2K1, TP53, DUSP1, and FOS, suggesting its role in signal transduction, stress response, and neuronal activity. A 200-nanosecond molecular dynamics simulation was conducted to analyze the behavior of the Cannflavin A-MAPK3 complex. Important structural measures—such as RMSF, RMSD, SASA, and radius of gyration (Rg)—confirmed that the complex was stable. Additionally, MM-GBSA analysis showed that it had strong binding free energy. When compared to standard antidepressants like Paroxetine and Amitriptyline, Cannflavin A was found to interact with key residues of the MAPK3 protein, suggesting it may have promising therapeutic potential. These findings highlight the promise of natural compounds in MDD treatment and provide a foundation for further in vivo and in vitro investigations toward the development of safer and more effective antidepressant therapies.
Keywords: Major Depressive Disorder (MDD) is a prevalent neuropsychiatric disorder with limited treatment efficacy and significant side effects associated with conventional antidepressants